Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan di Alfamidi Tinambung Kabupaten Polewali Mandar - Indah Sari; Erwin Erwin; Rahmat Ghazali (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of service quality and product quality on customer satisfaction at Alfamidi Tinambung, Polewali Mandar Regency. This study uses a quantitative approach with a causal-associative design. A sample of 100 respondents was determined using the Lemeshow formula with a purposive sampling technique. Data were collected through a 1–5 Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that partially, service quality (t-count = 5.700 > t-table = 1.984; sig. = 0.000) and product quality (t-count = 4.576 > t-table = 1.984; sig. = 0.000) have a positive and significant effect on customer satisfaction. Simultaneously, both variables also have a significant effect (F-count = 79.456 > F-table = 3.09; sig. = 0.000) with a contribution of 62.3% (R Square = 0.623). Thus, all three hypotheses are accepted. This study recommends improving employee responsiveness and product availability management.